The Influence Of Celebrity Endorser, Personal Selling And Pricing Strategy On Teenage Customers Response Toward Prepaid Card Products - Ratnawita Ratnawita; I Wayan Gede Antok Setiawan Jodi; Vivid Violin; Agus Nurofik; Dian Arlupi Utami (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
One of the promotional techniques used to transmit messages and change consumer attitudes is advertising. The appropriate media must be used if messages are to be effectively delivered to customers. The growth of Indonesia's information media has led to an overabundance of advertisements in the news. Television, radio, magazines, newspapers, and other forms of media are utilized. In particular in Indonesia, where consumers are still brand-conscious and brands that have appeared in television advertisements are more well-liked than those that have not, television advertising is still seen as the most efficient method of product promotion. The purpose of this study is to examine adolescent consumer reaction characteristics in relation to price, personal selling activities and salespeople (personal selling), and the usage of celebrities as advertising supports in television media. Multiple linear regression analysis is the method employed. SPSS was used to calculate the analytical process. Purposive sampling methods were used to distribute questionnaires to 100 teenage male and female respondents in Jakarta in order to gather primary data. The results of this research show that the use of celebrity endorsers in television advertising, personal selling, and price has a significant simultaneous and partial effect on the response of teen consumers in Jakarta. The price variable has a dominant influence on the response of adolescent consumers.